Synthesis of alginate-synthetic and chitosan-synthetic polymer semi-IPN xerogels for the removal of As(V) and Cu(II) ions - Alsamman-, M (SPRINGER, 2025)
This study involves the removal of As(V) and Cu(II) ions using xerogels of PClAETA/chitosan and PIA/alginate, respectively. The limited understanding of the adsorption mechanism, the low adsorption value of commercial products, and the difficulty of arsenic adsorption are reasons behind this study. These xerogels were synthesized via free radical synthesis and characterized using FTIR and TGA-DTG techniques, determining their adsorption and the kinetic model. At room temperature and pH 9, batch adsorption experiments showed that PClAETA/chitosan had an As(V) adsorption capacity of 82.3 mg/g at lower concentrations, with rapid adsorption occurring within 45 min. In the adsorption study of PClAETA/chitosan, a removal efficiency of 76% and an adsorption capacity of 30 mg/g were achieved at 60 degrees C for a solution concentration of 100 mg/L. Meanwhile, at pH 4.5 and lower concentrations, PIA/alginate demonstrated a Cu(II) adsorption capacity of 93 mg/g, with rapid adsorption occurring within approximately 5 min. The development and characterization of novel semi-IPN xerogels with scalable adsorption properties may have promising applications in wastewater treatment in the future, where using a combination of polymers with different properties allows for materials with enhanced and diverse properties, aiming to overcome the drawbacks of the individual polymer network and provide better mechanical properties and chemical resistance. The aim of this research is to obtain gels for heavy metal adsorption, break down conventional hydrogels, and provide a theoretical basis for the development of adsorption materials with higher capacity. [GRAPHICS]
Keywords: Semi-interpenetrating polymer networks; Adsorption; Alginate; Arsenic; Chitosan; Copper; Xerogels; Water purification